Peran Mahasiswa Kuliah Kerja Nyata dalam Pemulihan Ekonomi di Desa Ngaglik: Study tentang Pemulihan Ekonomi pada UMKM Jamur Krispi Mak Rin - Yofa Meilia Putri; Silvy Rahmawati; Vita Nerizza Permai (Penerbit Goodwood, 2023)
Purpose: The purpose of this activity is to improve the economy of MSME actors and make them more knowledgeable about technology for their businesses. Methodology: The implementation of activities, the approach used in this activity is through surveys, interviews, and capacity building. Results: The results of community service can be in the form of solving problems faced by the community by utilizing the expertise of the relevant academic community. With three stages of implementation, namely the pre-activity stage, the activity implementation stage and the post-activity stage, it can be concluded that: (1) UMKM Mushroom Crispy Mak Rin already have a good record of income and expenses and are able to record all transactions smoothly; (2) UMKM Mushroom Crispy Mak Rin are finally able to operate shopee well, and they now have several orders through the Shopee application, and their offline orders are also increasing. Even an increase of about 50-90% compared to before participating in mentoring; (3) UMKM Mushroom Crispy Mak Rin initially only used ordinary clear plastic and makeshift labels for their products, but after providing assistance with students they now have attractive labels and packaging; and UMKM Mushroom Crispy Mak Rin got new insights about things they didn't know, and they got new insights on how to make their businesses grow. Limitations: Time is too short and coincides with many activities that occur in August. Contribution: In the student environment, the scope of SMEs and the scope of the university.